Differential gene expression in Escherichia coli following exposure to non-thermal atmospheric-pressure plasma - Sharma, Ashish, author; Collins, George, advisor; Pruden, Amy, advisor (Colorado State University. Libraries, 2008)
Plasma decontamination provides a low temperature and non-toxic means of treating objects where heating and exposure to poisonous compounds is not acceptable especially in applications relating to medical devices and food packaging. The effects of various plasma constituents (UV photons, reactive species, charged particles etc.) acting independently and/or synergistically on bacteria at the biomolecular level is not well understood. High-density oligonucleotide microarrays were used to explore the differential gene expression of the entire genome of E. coli following plasma treatment. The results indicate a significant induction of genes involved in DNA repair and recombination suggesting that plasma exposure caused substantial DNA damage in the cell. There was also evidence of oxidative stress and suppression of genes involved in housekeeping functions of energy metabolism and ion transport. Experiments were also carried out to optimize plasma operating parameters to achieve a higher rate of inactivation of microbes. Overall, the results of this study will help to further optimize non-thermal plasma applications for bacterial inactivation.
Keywords: decontamination; plasma; sterilization; electrical engineering